(3TQM YbGFO GdfSais - (3eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, SYO GdOjf , J (B793 (3g` s; (3YeQ Hf eMeO Hf CMeO Hf ESeGYjd, CHh MaU, fLe GdOjf GdfSaj,J (B537 (3g` s ((3jhSa GdaGjcfi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HLdGd PGJg hceGd UaGJg hHYO aEf eHfi Yde GdTQGFY hCSGS bhGYO YbGFO GdESdGe gh Yde GdJhMjO hGdUaGJ hCf GdeNJUQ GdeSei HGdYbGFO ddEeGe YeQ GdfSai jTJed ef gPG Gdaf s
(3BNQgG (B:s
(3hEXgGQ ddBKGQ GdbhjI dG ai eWdb GdTQa hGdceGd adG OdGdI Ydi CaVdjI GdedGFcI hGddg CYde HGdMbjbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds